Hubungan Konsumsi Makanan Jajanan (Kariogenik) Dengan Kejadian Karies Gigi Pada Anak Prasekolah Di TK Aisyiyah Bustanul Athfal - Ermawati; Nurfatma Awalliyah Habib (Jurnal Sains & Kesehatan, 2025)
Dental caries is common in children because they tend to prefer sweet foods and drinks that can cause tooth decay. In general, children's oral hygiene is worse because they consume more caries-causing foods and drinks than adults. Cariogenic foods are foods that can cause tooth decay. Cariogenic foods are high in carbohydrates, sticky, and easily disintegrate in the mouth. The relationship between carbohydrate consumption and tooth decay is related to plaque formation on the tooth surface. Plaque forms from food debris stuck between teeth. This plaque eventually becomes the site of bacterial growth that converts glucose into acid, lowering the oral pH to 4.5. Under these conditions, the structure of tooth enamel dissolves. This quantitative study used a cross-sectional design with a total sample of m71 respondents. Exhaustive sampling was used, and questionnaires and observation sheets were used as instruments. Data analysis used univariate and bivariate analysis. The results of the study showed that of the 71 respondents studied, 43 children (60.6%) suffered from caries and 54 children (76.1%) consumed street food (cariogenic) with a Chi-Square analysis of P value = 0.001 <α value = 0.05 so that H0 was rejected and Ha was accepted. Based on the results of the study, it was concluded that there is a relationship between street food consumption (cariogenic) in preschool children at Aisyiyah Bustanul Athfal Kindergarten).